Valgus subsidence of the tibial component in cementless Oxford unicompartmental knee replacement - Liddle, A. D. (Bone Joint J, 2014)
The cementless Oxford unicompartmental knee replacement has been demonstrated to have superior fixation on radiographs and a similar early complication rate compared with the cemented version. However, a small number of cases have come to our attention where, after an apparently successful procedure, the tibial component subsides into a valgus position with an increased posterior slope, before becoming well-fixed. We present the clinical and radiological findings of these six patients and describe their natural history and the likely causes. Two underwent revision in the early post-operative period, and in four the implant stabilised and became well-fixed radiologically with a good functional outcome. This situation appears to be avoidable by minor modifications to the operative technique, and it appears that it can be treated conservatively in most patients. Cite this article: Bone Joint J 2014;96-B:345–9.